Medical Genetics at a Glance - Dorian J. Pritchard (Blackwell Science, 2003)
"Medical Genetics at a Glance fits the budget and reading time of medical students and those seeking a quick introduction to this fast-moving field. It is recommended as primary or supplementary reading in a lecture-based course or for exam preparation."--BOOK JACKET.